Analisis Yuridis Putusan Nomor 1244 K/PID/2017 tentang Sengketa Penguasaan Tanah dalam Perspektif Kesalahan Penerapan Hukum oleh Hakim - Tiara Mauliza (CV. Creative Tugu Pena, 2024)
Land disputes often lead to complex legal issues, particularly when there are errors in the application of law during judicial proceedings. Decision Number 1244 K/PID/2017 serves as the object of analysis to identify judicial errors in applying the law in a criminal case related to the control of harvest yields on land previously adjudicated in a civil case. This study aims to evaluate the judge's decision from a legal perspective, using a qualitative literature study method focused on analyzing legal documents, legislation, and related court decisions. The data used include legal provisions such as Article 16 paragraph (1) of the Agrarian Law (UUPA), Article 362 of the Criminal Code (KUHP), and Article 233 paragraph (1) of the Criminal Procedure Code (KUHAP), as well as related jurisprudence. The analysis results reveal that the appellate-level judge erred in assessing the existence of an appeal memorandum, which should not be an absolute requirement as stipulated in the Criminal Procedure Code. The judge failed to integrate criminal law facts, thereby undermining the principles of legal certainty and justice. The conclusion of this study emphasizes the need to strengthen judges' understanding of legal principles and the relevance of legal norms in complex cases to prevent decisions that harm the principle of justice.